Performance of hot and warm mix asphalt mixtures enhanced by nano-sized graphene oxide. (30th August 2019) - Zhu, Juncai; Zhang, Kun; Liu, Kefei; Shi, Xianming
Highlights: The modification effects of graphene oxide combined with different warm mix additives on asphalt mixtures are studied. Graphene oxide has significant benefits on the moisture resistance and high-temperature rutting resistance of asphalt mixtures. Waste cooking oil can effectively improve the thermal cracking resistance of GO-modified asphalt mixture. Graphene oxide can effectively improve the (oxidative) aging resistance of asphalt mixture. Abstract: The objective of this laboratory study was to evaluate the performance of hot mix asphalt (HMA) and warm mix asphalt (WMA) mixtures modified by graphene oxide (GO). The base asphalt has a 60/80 penetration grade and the warm mix additives are Sasobit and waste cooking oil (WCO), which were added at 3% and 5% by weight of asphalt binder, respectively. The performance of HMA and WMA mixtures was evaluated. The experimental results indicate that the addition of GO at 0.05% by weight of binder significantly increased the mixing and compaction temperatures of base asphalt mixture, whereas the addition of warm mix additive, either Sasobit or WCO, can effectively reduce the construction temperatures of GO modified asphalt mixture. The addition of GO can significantly improve the moisture resistance, high-temperature rutting resistance, and compressive resilient modulus of asphalt mixture, but slightly compromise its low-temperature cracking resistance. In addition, Sasobit can compatibly work with GO to improve the performance of asphalt mixtures, and WCO can effectively improve the low-temperature cracking resistance of GO modified asphalt mixture. Aging test results showed that GO can enhance the (oxidative) aging resistance of asphalt mixtures, reduce the moisture susceptibility of the aged mixtures, and mitigate the detrimental impact of aging on their low-temperature performance.